Technology in education through mobile learning application (MLA) and its impact on learning outcomes: Literature review - Budiarto, Mochamad Kamil; Gunarhadi, Gunarhadi; Rahman, Abdul (Intelektual Pustaka Media Utama, 2024)
Integration of information and communication technology (ICT) in teacher education is a means to support the teaching and learning process. Good teaching by utilizing technology certainly requires changes, especially in the realm of pedagogy, but teachers apparently do not have enough ability to optimize ICT in the learning process. In fact, ICT has the potential to provide various benefits for teachers and students, including joint learning areas, cooperative and collaborative learning opportunities. Therefore, this research aims to identify the use of mobile learning application (MLA) and its impact as a form of ICT integration in learning. The method used is literature study, by taking data from various relevant scientific articles and books. Data analysis uses descriptive analysis from the results of the synthesis of several literature reviews obtained. The research results show that a number of 10 main articles and 15 relevant supporting articles as well as several book sources show that mobile-based learning with smartphone devices is becoming a trend at various levels of education, both academic and vocational.